Peran Mediasi Motivasi Kerja terhadap Kepemimpinan Transformasional dan Knowledge Sharing dalam Meningkatkan Kinerja Karyawan - Hidayat, Muhammad Alif; Zamrudi, Muhammad Faisal Yul (Lembaga Yasin AlSys, 2026)
This study was motivated by fluctuations in the achievement of production targets, as well as employee absenteeism and tardiness levels in the production division of PT Bahana Buana Box Demak, which indicate the need for more effective human resource management to improve employee performance. This study aimed to analyze the effect of transformational leadership and knowledge sharing on employee performance, with work motivation as a mediating variable. This study used a quantitative approach with an explanatory research method. Data were obtained through the distribution of questionnaires to 160 employees of the production division of PT Bahana Buana Box selected using purposive sampling. Data analysis was conducted using the Partial Least Squares (PLS) method with the SmartPLS application. The results showed that transformational leadership had a positive and significant effect on work motivation and employee performance. Knowledge sharing was also proven to have a positive and significant effect on work motivation and employee performance. In addition, work motivation was able to mediate the effect of transformational leadership and knowledge sharing on employee performance. Thus, this study affirms that improving employee performance can be achieved through the implementation of transformational leadership, the strengthening of a knowledge-sharing culture, and the optimization of work motivation within the company. The practical implications of this study indicate the importance of human resource management strategies oriented toward inspirational leadership, knowledge collaboration, and motivational reinforcement as a basis for improving employee performance in the production division.